Reconstructive flap surgery in head and neck cancer patients: an interdisciplinary view of the challenges encountered by radiation oncologists in postoperative radiotherapy - Thariat, Juliette; Carsuzaa, Florent; Beddok, Arnaud; Deneuve, Sophie; Marcy, Pierre-Yves; Merlotti, Anna; Dejean, Catherine; Devauchelle, Bernard (Frontiers in Oncology, 2024)
Background: Major advances have been made in reconstructive surgery in the last decades to reduce morbidity in head and neck cancer. Flaps are now present in 80% of patients with oral cavity cancer to cover anatomic, functional and cosmetic needs. However, gaps in interdisciplinary innovation transfer from surgery to postoperative radiotherapy (poRT) remains challenging. We aimed to provide an interdisciplinary view of the challenges encountered by radiation oncologists in planning head and neck postoperative radiotherapy. Methods: a systematic and critical review was conducted to address areas of optimization in surgery and radiology that may be relevant to poRT. Results: Despite extensive surgical literature on flap techniques and salvage surgery, 13 retrospective series were identified where flap outcomes were indirectly compared between surgery alone or poRT. These low-evidence studies suggest that radiotherapy accelerates flap atrophy, fibrosis, osteoradionecrosis and deteriorates functional outcomes. Preliminary evidence suggests that tumor spread occurs at the flap-tissue junction rather than in the flaps. One prospective 15-patient study showed 31.3% vs 39.2% flap volume reduction without or with poRT. In an international consensus, experts recognized the needs for optimized flap-sparing poRT against flap-related functional deterioration and bone damage. CT, MRI and PET-CT modalities show potential for the delineation of the junction area between native tissues and flap, for flap segmentation and to characterize flap-specific changes quantitatively and correlate them with patterns of relapse or complications. Conclusion: Flap management in poRT is insufficiently documented but poRT seems to damage flaps.Current gaps in knowledge underscores the need for prospective flap assessment and interdisciplinary trials investigating flap morbidity minimization by flap-sparing poRT planning.